Pembulatan Tarif dalam Usaha Sewa Game PlayStation: Tinjauan Etika Bisnis Islam dan Hukum Positif Indonesia di Kecamatan Barat, Magetan - Wantini, Enjelia Nur; Umami, Khairil (Jurnal Antologi Hukum, 2025)
The development of digital entertainment businesses, particularly Game PlayStation rental services, has given rise to various business practices that are not always aligned with ethical principles and legal regulations. One common practice is the unilateral rounding up of rental fees without prior notification or consent from consumers. This study aims to examine the practice of rental fee rounding in Game PlayStation rental services in Barat Subdistrict, Magetan, from the perspectives of Islamic business ethics and Indonesian positive law. The research employs a qualitative approach with a socio-juridical method, integrating normative legal analysis with empirical field data. Data were collected through direct observation, in-depth interviews with business owners, employees, and consumers, as well as supporting documentation. The findings reveal that fee rounding predominantly occurs in the personal rental system and is carried out without transparent information provided to consumers. Although perceived as a common practice by business actors, this practice creates information asymmetry and weakens consumers’ bargaining position. From the perspective of Islamic business ethics, such practices contradict the principles of tawhid, justice, honesty (ṣidq), responsibility (mas’ūliyyah), and mutual consent (tarāḍī), and contain elements of uncertainty (gharar). From the standpoint of positive law, the practice violates Regulation of the Minister of Trade of the Republic of Indonesia No. 35/M-DAG/PER/7/2013 and Law No. 8 of 1999 on Consumer Protection. This study concludes that fee rounding without prior disclosure constitutes both ethical and legal deviations, highlighting the need to strengthen ethical awareness, tariff transparency, and legal guidance for micro-scale business actors in the digital entertainment sector.